2023
DOI: 10.3390/ijms24054556
|View full text |Cite
|
Sign up to set email alerts
|

Psoriatic Resolved Skin Epidermal Keratinocytes Retain Disease-Residual Transcriptomic and Epigenomic Profiles

Abstract: The disease-residual transcriptomic profile (DRTP) within psoriatic healed/resolved skin and epidermal tissue-resident memory T (TRM) cells have been proposed to be crucial for the recurrence of old lesions. However, it is unclear whether epidermal keratinocytes are involved in disease recurrence. There is increasing evidence regarding the importance of epigenetic mechanisms in the pathogenesis of psoriasis. Nonetheless, the epigenetic changes that contribute to the recurrence of psoriasis remain unknown. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Recent therapies are able to induce complete resolution of the symptoms, but if treatment is suspended, symptoms may occur again very often at the same body sites, indicating that in resolved lesions a molecular scar remains 10 , and epigenetic changes detected in epidermal keratinocytes of resolved skin may be responsible for the disease residual transcriptomic profile found in the same regions 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent therapies are able to induce complete resolution of the symptoms, but if treatment is suspended, symptoms may occur again very often at the same body sites, indicating that in resolved lesions a molecular scar remains 10 , and epigenetic changes detected in epidermal keratinocytes of resolved skin may be responsible for the disease residual transcriptomic profile found in the same regions 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the DNA methylation pattern does not change completely in lesional skin after treatment, epigenetic changes could contribute to this local memory [ 110 ]. In fact, differential methylation patterns have been identified between paired never-lesional skin and resolved lesions of psoriasis patients [ 111 ]. Furthermore, methylation differences between never-lesional psoriatic skin and healthy skin from volunteers, involving the Wnt and cadherin pathway genes, have also been identified and suggest that uninvolved skin might signify a pre-psoriatic condition with underlying disease susceptibility [ 112 ].…”
Section: Resultsmentioning
confidence: 99%
“…For what concerns the expression of DNA demethylases, we noticed a general downregulation of their level in vaginal keratinocytes after discontinuous PE N/MPL exposure. It has been proposed that reduced levels of TET1 and, subsequently, 5-hydroxymethylcytosine cause the impaired self-renewal of stem cells [64]; Liu et al demonstrated that TET2 regulated cell viability, apoptosis and the expression of inflammatory mediators in keratinocytes [65]; Ghaffarinia et al observed diminished 5-methylcytosine and 5-hydroxymethylcytosine amounts, and decreased mRNA expression of TET3 in psoriatic epidermis [66]. Even if little is known about the role of epigenetic enzymes in keratinocyte biology, overall, our findings suggest that the dysregulation of DNMTs and TETs levels upon N/MPL exposure might accelerate processes leading to vaginal cell ageing.…”
Section: Discussionmentioning
confidence: 99%